STUDI FENOMENOLOGI FINANCIAL LITERACY PENGRAJIN LOGAM DI PROPINSI JAWA TIMUR - Riani, Lilia Pasca (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
The purpose of this study is describing condition mapped of metalcrafters financial literacy in the province of East Java. The research uses a qualitative approach by implementing a phenomenological study. Data collection technique used in-depth interviews with eight metalcrafters. The results of this study are researchers obtained a 4-dimensional shape of a metalcrafters financial literacy in East Java, which is the dimension of knowledge about financial terminology, dimension of money management, the dimensions of financial record and system of work, and an explain the condition of financial literacy metalcrafters about knowledge about taxes.